Phenotypic spectrum and genetic heterogeneity of cystic fibrosis in Sri Lanka - Neluwa Liyanage Ruwan Indika; Dinesha Maduri Vidanapathirana; Hewa Warawitage Dilanthi; Grace Angeline Malarnangai Kularatnam; Nambage Dona Priyani Dhammika Chandrasiri; Eresha Jasinge (BMC, 2019)
Abstract Background Cystic fibrosis has been largely under-diagnosed and thus, limited data is available on the incidence of cystic fibrosis in Sri Lanka. Our aim is to describe the phenotypic and genotypic spectrum of children with cystic fibrosis in Sri Lanka. Case presentation This report describes 10 unrelated cystic fibrosis cases with phenotypic features of cystic fibrosis and abnormal or intermediate sweat tests. The most common phenotypic features in this sample of symptomatic patients were persistent or recurrent lower respiratory tract infections, failure to thrive and Pseudo-Bartter syndrome. Altogether 7 cystic fibrosis causing mutations were identified in 10 patients. Except delta F508 which is the commonest mutation worldwide all the other mutations detected in Sri Lankan patients are rare mutations. 1161delC and V456A detected in our patients are South Asian mutations. The other mutations such as [C.1282C > G; C.2738A > G], C.53 + 1G > C, 2184insA and a deletion encompassing exons 4 to 11 have been reported previously from European patients with cystic fibrosis. Conclusion These cases highlight the importance of considering the diagnosis of cystic fibrosis in children and young adults presenting with persistent respiratory tract infections associated with severe malnutrition and Pseudo-Bartter syndrome, especially in low income countries where newborn screening for cystic fibrosis is not available. The spectrum of CFTR mutations in Sri Lanka is heterogeneous and possibly linked to genetic flow from Indian subcontinent and Europe. The common mutations should be identified by sequencing the entire CFTR gene in adequate number of cystic fibrosis patients in order to design a mutation panel for common regional mutations.